Ultrasound Velocity Analysis for Molecular Interactions in Binary Liquid Mixtures of Cumene and Propanone-2 across Variable Temperatures - Abhishek Kumar Singh; Danveer Singh Yadav (South Eastern European Journal of Public Health, 2025)
Presented study explores molecular interactions in binary liquid mixtures of cumene and propanone-2 through the measurement of ultrasonic velocity, density, and viscosity at temperatures of 303 K, 308 K, and 313 K. The derived acoustic and thermodynamic parameters—including isentropic compressibility, intermolecular free length, molar volume, relaxation time, and Rao’s constant—were systematically analyzed to elucidate interaction mechanisms at the molecular level. Additionally, excess parameters were computed to assess deviations from ideal behavior, providing deeper insights into molecular association and structural modifications induced by temperature variations. The findings reveal prominent dipole-dipole interactions between the constituent molecules, modulated by thermal effects, highlighting the complex interplay of cohesive and dispersive forces in polar liquid mixtures. This research advances the fundamental understanding of liquid-phase interactions, offering valuable implications for industrial and chemical applications, including solvent formulation, reaction dynamics, and material design.